Health-care associated infections in children after cardiac surgery in a pediatric cardiac intensive care unit (PCICU) - Naveed -ur-Rehman Siddiqui; Fatima Mir; Omair Shakil; Muneer Amanullah; Anwarul Haque (Journal of Infection in Developing Countries)
This item has no abstract. Follow the links below to access the full text.